A facile one-step synthesis of star-shaped alkynyl carbonates from CO2. Issue 56 (16th June 2015) - Hui Khoo, Rebecca Shu; Lee, Agnes Mei Xian; Braunstein, Pierre; Andy Hor, T. S.; Luo, He-Kuan
Abstract : The synthesis of new star-shaped compounds containing three or six pendant carbonates with terminal alkynes at 1 atm CO2 and room temperature. Abstract : We report a facile, one-step green synthesis of two new star-shaped compounds containing three or six pendant carbonate groups with terminal alkynes. The reaction occurs under 1 atm CO2 and proceeds optimally at room temperature. These multialkynyl-carbonate-functionalized benzenes represent readily accessible precursors to more complex dendritic materials.